First Aid Training for Accidents in Recreational Sports Tourism - Siregar, Nofi Marlina; Novita Sari, Eka Fitri; Ali, Masnur; Asri, Novri (International Journal of Public Devotion, 2025)
Recreational sports tourism activities involving the community and educational institutions such as elementary schools are often accompanied by the risk of minor to moderate accidents, such as injuries, sprains, fainting, and even broken bones. Unfortunately, community preparedness in providing first aid for accidents (P3K) is still relatively low due to the lack of systematic training and education. Therefore, this community service activity aims to improve the capacity of sports teachers and residents around SDN Kamasan 01, Serang Regency, in handling emergency incidents through practice-based P3K training. The implementation method includes interactive lectures, P3K technique displays, case simulations, and distribution of pocket modules to 40 participants. Evaluation was carried out through pretest-posttest and direct observation during the simulation. The results of the training showed a significant increase in the knowledge and skills of participants, with an average increase of 68% and 85% of participants were able to disseminate basic P3K techniques correctly. This activity proves that community-based P3K training is effective in building an emergency response culture and improving the safety of recreational sports activities. It is hoped that similar activities can be replicated in other schools and communities as part of community safety education.Pelatihan Pertolongan Pertama pada Kecelakaan Di Wisata Olahraga RekreasiABSTRAKKegiatan wisata olahraga rekreasi yang melibatkan masyarakat dan institusi pendidikan seperti sekolah dasar sering kali diwarnai dengan risiko kecelakaan ringan hingga sedang, seperti luka, terkilir, pingsan, bahkan patah tulang. Sayangnya, kesiapsiagaan masyarakat dalam memberikan pertolongan pertama pada kecelakaan (P3K) masih tergolong rendah akibat kurangnya pelatihan dan edukasi yang sistematis. Untuk itu, kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas guru olahraga dan warga sekitar SDN Kamasan 01, Kabupaten Serang, dalam menangani kejadian darurat melalui pelatihan P3K berbasis praktik. Metode pelaksanaan meliputi ceramah interaktif, demonstrasi teknik P3K, simulasi kasus, dan pembagian modul saku kepada 40 peserta. Evaluasi dilakukan melalui pretest–posttest serta pengamatan langsung saat simulasi. Hasil pelatihan menunjukkan peningkatan signifikan pada pengetahuan dan keterampilan peserta, dengan rata-rata peningkatan nilai sebesar 68% dan 85% peserta mampu mempraktikkan teknik P3K dasar dengan tepat. Kegiatan ini membuktikan bahwa pelatihan P3K berbasis komunitas efektif dalam membangun budaya tanggap darurat dan meningkatkan keamanan kegiatan olahraga rekreasi. Diharapkan, kegiatan serupa dapat direplikasi di sekolah dan komunitas lain sebagai bagian dari edukasi keselamatan publik.Kata Kunci:Pertolongan Pertama; Wisata Olahraga; P3K; Masyarakat; Sekolah Dasar